PENERAPAN SAFETY MANAGEMENT SYSTEM (SMS) DAN KOMPETENSI PEMANDU LALU LINTAS PENERBANGAN - Anaria Carini Melissa; Toto Hardiyanto Subagyo; Hadi Suharno; Suharto Abdul Majid (Institut Transportasi dan Logistik Trisakti, 2017)
The objective of the research is to analyze the influence between Implementation of Safety Management System (SMS) and Competency of Air Traffic Controller towards Aviation Safety at Perum LPPNPI Main Branch JATSC. Type of research is quantitative research by means of surveys, where data obtained through a questionnaire that will be distributed On Air Traffic Controller Perum LPPNPI Main Branch JATSC. The population in this research is an Air Traffic Controller Perum LPPNPI Main Branch JATSC totaled 356 (Three Hundred and Fifty Six) people. The sample taken is 100 (hundred) people. Data collected through the instrument in the form of a questionnaire. Methods of data analysis performed in this study using correlation and regression. The results of data analysis can be concluded that : (1) Implementation of Safety Management System (SMS) has a positive and significant impact on Aviation Safety (2) Competency of Air Traffic Controller has a positive and significant impact on Aviation Safety (3) Implementation of the Safety Management System (SMS) and Competency of Air Traffic Controller has positive and significant impact together on Aviation Safety. The implications of the research are Aviation Safety can be improved by upgrading Implementation of Safety Management System (SMS) and Competency of Air Traffic Controller.